Neofusicoccum arbuti: a hidden threat to Arbutus menziesii characterized by widespread latent infections and a broad host range. Issue 1 (2nd January 2016) - McGregor, Rob Roy; Sakalidis, Monique L.; Hamelin, Richard C.
Abstract: The iconic tree species, Arbutus menziesii (Pacific madrona, madrone arbutus), has been in decline in the Pacific Northwest of North America for the past 40 years. It is thought that the fungal pathogen Neofusicoccum arbuti has contributed to the decline of this tree species. In recent years, there have been reports of declining arbutus in the coastal region of southern British Columbia, Canada. We conducted intensive sampling in a park with severely affected arbutus trees to determine the cause and prevalence of decline. The majority of arbutus trees sampled in this study had cankers associated with N. arbuti infection. We also sought to determine if N. arbuti has additional hosts that could act as a reservoir for this pathogen. Six new hosts of N. arbuti were identified, and a seventh was confirmed; these hosts spanned four taxonomic orders and included Amelanchier alnifolia, Cytisus scoparius (confirmed), Gaultheria shallon, Ilex aquifolium, Rosa sp., Sorbus sitchensis and Spiraea douglasii . Recovery of Neofusicoccum arbuti from both symptomatic and asymptomatic plant tissues of these hosts indicates that it potentially has a broad host range. It remains to be established if N. arbuti is also pathogenic to these hosts. These results highlight the importance of monitoring for this pathogen and assessing the extent of its geographic distribution and its ability to colonize various hosts.